The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.24990/injec.v5i1.269
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Humidity, Temperature, and Noise With Sleep Quality at Intensive Care Unit (ICU)

Abstract: Introduction: Temperature, humidity, and noise are factors that affect sleep quality. The objective of the research is to determine the effect of humidity, temperature, and room noise on sleep quality of (Intensive Care Unit) ICU patients. Methods: A quantitative research with the cross-sectional approach, involving 84 patients taken by consecutive sampling, with the inclusion criteria of at least having already spent more than two days in ICU, having age between 20-70 years, and being conscious and cooperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In a previous study, wherein the median noise level in the ICU was similar to that in the present study, noise was the only factor that significantly influenced patients’ sleep quality. 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, wherein the median noise level in the ICU was similar to that in the present study, noise was the only factor that significantly influenced patients’ sleep quality. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Studies that showed significant noise reduction implemented some innovative strategies such as ‘Quiet Time’, 31 referring to when changes in staff behaviour aimed to produce less noise. The literature shows that noise reduction can be achieved, as much of the noise source is avoidable 30 and comes from infusion equipment, monitors with maladjusted vital parameter alarms, and conversations among health professionals. 32 , 33 Thus, training and awareness of nursing staff on the importance of the topic could have significantly influenced the decrease in the noise level.…”
Section: Discussionmentioning
confidence: 99%
“…Elliott et al (2013) found several factors associated with sleep disturbances among critically ill patients in ICU were noise, lighting, interventions provided by nurses, treatment and patient illnesses (Elliott et al, 2013). Environmental noise in the ICU may result in psychological disorders such as agitation, confusion and delirium and physiological such as cardiovascular disorders and suppression of the immune response to infection or delayed healing as well as an increased need for drugs (Suparti and Suroso, 2020). Boyko et al (2012) stated that ICU noises are a major problem for critically ill patients due to medical measures such as the sound of monitors, voices of visitors, conversations between nurses which often cause sleep disturbances and lighting that is too bright so patients are easy to wake up (Boyko, Ørding and Jennum, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disorders in ICU patients can be handled by adjusting the lighting level to help patients feel calm and comfortable (Engwall et al, 2015). Another study by Suparti (2020) found that sleep quality can be improved by managing the ICU's environment, such as lowering the voice of staff conversations, lowering lighting, and arranging routine maintenance activities at night (Suparti and Suroso, 2020). Furthermore, Hu (2010) found that sleep disturbances in critically ill patients can be overcome by using ear plugs and eye masks not only to improve sleep quality but also to increase melatonin production .…”
Section: Introductionmentioning
confidence: 99%
“…Gangguan tidur pasien di ICCU dapat ditangani dengan memodifikasi lingkungan yaitu pencahayaan berkurangnya sistem pencahayaan pada di area pasien dapat membuat pasien merasa nyaman dan tenang (Suparti & Suroso, 2020). Penanganan pasien kritis yang mengalami kesulitan tidur di ruang ICCU umumnya diberikan obat untuk meminimalkan terjadinya kegelisahan yang berdampak kesulitan tidur (Akpinar et al, 2022).…”
unclassified